Knowledge Sharing Penggunaan Aplikasi Pengarsipan Elektronik dengan IWSM dan Aplikasi Wordpress di Mitra SMKN 1 Cisarua - Mamun Sutisna; Ermina Tiorida; Mohammad Rizal Gaffar; Tangguh Dwi Pramono; Mukaram Mukaram; Yayan Firmansyah (Jurnal Pengabdian Masyarakat Madani, 2021)
The new curriculum which revises the SMK 2018, revised curriculum focuses on the used information and telecommunications technology. These curriculum have several renewals such as the emergence of the name office automation and governance and also the emergence of subjects with availability of digital and technology. One of the subjects highlighted was electronic archiving to answer these challenges. The purpose of this service were to improve the competence of teachers and staff of SMKN Cisarua in the field of electronic filing systems with the IWSM program and the introduction of the wordpress application. This service method hybird. Delta, the results of the evaluation of the average post test score compared to  pree test, increased by 18%, this shows a positive result. With the attendance rate of participants for 5 days of training of 82,4%. This indicates that the high enthusiasm of the participants.